High-resolution observations of longitudinal fronts in a well-mixed tidal channel - Wang, Daoling; Lu, Shasha; Xie, Zhongyu; Xia, Xiaoming; Liu, Yifei (Frontiers in Marine Science, 2024)
Longitudinal front is important for coastal dynamics, with crucial implications for sediment and pollutant transport required for coastal management. Three conventional theories have been proposed to explain the generation mechanisms of the longitudinal fronts. However, they are not completely supported by preliminary observation results within the Tiaozhoumen channel. Therefore, a field survey covering the whole flood-ebb tide, including high-resolution observations of velocity and density, was conducted to analyse the intra-tidal change of the fronts. The results showed that the fronts were mainly determined by the velocity shear, while the density gradient and Coriolis effect were small and negligible. Velocity structures presented significant differences between flood and ebb tides. Low velocity close to zero was present near the frontal zone at the flood tide. However, a velocity difference between shallow and deep bathymetry existed at the ebb tide. The flood fronts appeared longer and stronger than the ebb tide fronts. The fronts at ebb tide might be related to the velocity shear, due to differential bottom friction at varied depths from shallow to deep, consistent with the traditional theory of longitudinal front formation. The front system at flood tide is distinguished from the conventional fronts mentioned. The large Reynolds number and high turbulent dissipation rates in the frontal zone suggest that the fronts may be related to the boundary layer separation from the island. These findings provide evidence of the relationship between flood fronts and boundary layer separation; nonetheless, further studies must be conducted for a complete theory.